Averrhoa carambola leaf from Depok, West Java, Indonesia: Phytochemistry characterization and prospective anti-candidiasis activity - Marina Ika Irianti, Berna Elya, Ratika Rahmasari, Nuraini Puspitasari, Fasya Hadaina Maharani, Muhareva Raekiansyah (Journal of Applied Pharmaceutical Science, 2021)
Candida albicans is a commensal microorganism that can be pathogenic in immunocompromised patients. Eradication of candidiasis is complicated by the resistance of the existing antifungal agents. Therefore, novel antifungal drug discovery is required for the efficient management of candida infections. The invention of antifungal from natural products has been stimulated by the increasing prevalence of drug resistance. The aim of this study is to evaluate the antifungal activities of Averrhoa carambola leaves, an Indonesian native plant. The antifungal activity was evaluated by conducting crystal violet (CV) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay to determine IC50 values. From the initial screening, the ethyl acetate fraction of A. carambola leaves showed inhibition against C. albicans growth. According to the microscopic observations, trichome was presented in both the upper and lower sides of the A. carambola leaves. The CV assay result confirms that C. albicans cells supplemented by the extract grew lower than the untreated cells by reaching more than 60% cell reduction compared to control. The MTT assay was carried out to assess the inhibitory effect on the cell viability (IC50 = 24 µg/ml). The thin layer chromatography results showed flavonoid and steroid contents in A. carambola leaves. The presence of flavonoid and steroid was subsequently confirmed by using liquid chromatographytandem mass spectrometry which showed two compounds, namely pinocembrin-7-neohesperidoside and spinasterol. This preliminary study indicated that A. carambola leaves are potential for anti-candidiasis drug development.
Keywords: Candida albicans, Averrhoa carambola leaves, crystal violet, anti-candidiasis, MTT assay